"Creative solutions": selling cigarettes in a smoke-free world. (25th February 2004) - Smith, E A; Malone, R E
Abstract : Objective: To analyse the development and execution of the "Creative Solutions" Benson & Hedges advertising campaign to understand its social, political, and commercial implications. Methods: Searches of the Philip Morris documents and Legacy Tobacco Documents websites for relevant materials; Lexis/Nexis searches of major news and business publications; and denotative and connotative analyses of the advertising imagery. Results: Philip Morris developed the Creative Solutions campaign in an effort to directly confront the successes of the tobacco control movement in establishing new laws and norms that promoted clean indoor air. The campaign's imagery attempted to help smokers and potential smokers overcome the physical and social downsides of smoking cigarettes by managing risk and resolving internal conflict. The slogans suggested a variety of ways for smokers to respond to restrictions on their habit. The campaign also featured information about the Accommodation Program, Philip Morris's attempt to organise opposition to clean indoor air laws. Conclusion: The campaign was a commercial failure, with little impact on sales of the brand. Philip Morris got some exposure for the Accommodation Program and its anti-regulatory position. The lack of commercial response to the ads suggests that they were unable to successfully resolve the contradictions that smokers were increasingly experiencing and confirms the power of changing social norms to counter tobacco industry tactics.